THE INDIA–WORLD BANK: HISTORICAL RELATIONSHIP - R. Venkatesh (RADJA PUBLIKA, 2023)
Abstract Cooperation between the World Bank and India goes back to the foundation of the International Bank for Reconstruction and Development (IBRD) in 1944. As one of 44 countries, India prepared the agenda for the Bretton Woods Conference in June 1944. The Indian delegation led by Sir Jeremy Raisman, Finance Member of the Government of India, proposed the name